2011
DOI: 10.1016/s0735-1097(11)62049-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Is Associated With Arterial Stiffness and Vascular Dysfunction in Healthy Humans

Abstract: Objectives-The primary objective of this study was to elucidate mechanisms underlying the link between vitamin D status and cardiovascular disease by exploring the relationship between 25-hydroxyvitamin D (25-OH D), an established marker of vitamin D status, and vascular function in healthy adults. Background-Mechanisms underlying vitamin D deficiency-mediated increased risk of cardiovascular disease remain unknown. Vitamin D influences endothelial and smooth muscle cell function, mediates inflammation, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(147 citation statements)
references
References 25 publications
7
137
3
Order By: Relevance
“…[13][14][15][16]30,31 Brachial-ankle PWV was found to be significantly lower in CKD patients with 25(OH)D deficiency. 15 It has been reported that flow-mediated dilatation as a marker of endothelial function was lower in vitamin D deficiency in patients with CKD, and improved with replacement of 25(OH)D. In addition, vitamin D supplementation significantly reduced biomarkers of endothelial dysfunction such as intracellular adhesion molecule (ICAM), vascular adhesion molecule (VCAM), endothelial leukocyte adhesion molecule (E-Selectin) and von Willebrand factor (vWF).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[13][14][15][16]30,31 Brachial-ankle PWV was found to be significantly lower in CKD patients with 25(OH)D deficiency. 15 It has been reported that flow-mediated dilatation as a marker of endothelial function was lower in vitamin D deficiency in patients with CKD, and improved with replacement of 25(OH)D. In addition, vitamin D supplementation significantly reduced biomarkers of endothelial dysfunction such as intracellular adhesion molecule (ICAM), vascular adhesion molecule (VCAM), endothelial leukocyte adhesion molecule (E-Selectin) and von Willebrand factor (vWF).…”
Section: Discussionmentioning
confidence: 93%
“…All these pathological processes result in decreased vascular compliance, increased vascular calcification and inflammation, which may contribute to the development of arterial stiffnesss. 3,15,16,27 Vitamin D deficiency is associated with cardiovascular disease, all-cause mortality, morbidity, poor clinical outcomes and rapid decline of eGFR in patients with CKD. 25,34,35 Our study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A couple of cross-sectional studies in healthy adults show lower serum levels of 25(OH)D to be associated with endothelial dysfunction (91,92) . A few trials show an improvement in flow-mediated dilation with vitamin D supplementation (93)(94)(95) , but most show no effect (79,(96)(97)(98) ( Table 2).…”
Section: Endothelial Functionmentioning
confidence: 99%
“…Many cross-sectional studies have shown inverse associations between vitamin D and arterial stiffness (91,(101)(102)(103)(104)(105)(106)(107) , but there are relatively few clinical trials that have investigated the effect of vitamin D supplementation (Table 2). Gepner et al conducted a study in which healthy postmenopausal women were randomised to 62·5 μg vitamin D 3 daily (n 57) or placebo (n 57) for 4 months.…”
Section: Arterial Stiffnessmentioning
confidence: 99%